Behavioral, experiential, and physiological signatures of mind blanking - Esteban Munoz-Musat; Arthur Le Coz; Andrew W. Corcoran; Laouen Belloli; Lionel Naccache; Thomas Andrillon (Proceedings of the National Academy of Sciences, 2025)
Does being awake necessarily mean being conscious of something? This study investigates the phenomenon of mind blanking (MB), characterized by an “emptiness of mind,” comparing it with mind wandering (MW) and on-task (ON) states. Using a sustained attention task and electroencephalogram monitoring, behavioral, and neurophysiological signatures of MB were examined in 62 participants. MB exhibited a specific pattern of behavioral lapses, as well as decreased fast oscillatory activity and complexity over posterior electrodes compared to MW. Functional connectivity analyses revealed decreased long-range interareal connectivity during MB, compared to both ON and MW states. Event-related potentials with source reconstruction and temporal decoding techniques indicated a significant disruption in visual processing during MB, starting from 200 ms post stimulus and echoing into the late-stage of visual processing, suggesting a disruption of conscious access to sensory information during MB. Electroencephalogram-derived markers allowed the prediction of mental states at the trial level, offering a finer view of conscious dynamics than subjective reports alone. Overall, these findings challenge the notion of the wakeful conscious mind as inherently content-oriented, suggesting that MB reflects genuine gaps in the stream of conscious thoughts, arising from disruptions in the generation or accessibility of thought content.